Olifants River irrigation schemes: reports 1 and 2. Report 1 - Crop and irrigation data for four separate irrigation schemes. Report 2 - Irrigation management structures for four separate irrigation schemes - Tren, R.; Schur, M. (International Water Management Institute, 2000)
Report 1 documents key data affecting crop budgets and water supply costs in several Olifants Basin irrigation schemes. The data will be used to develop an irrigation water-pricing model to describe supply-side and demand side forces. Report 2 investigates the management and operations of these schemes. It compares farming and irrigation practices in several different types of schemes - a government-run scheme, a private commercial scheme and two small irrigation schemes managed by black farmers.